Moderasi Beragama dalam Islam - Harahap, Elly Warnisyah; Sufriyansyah; Wedi Samsudi (Edukais : Jurnal Pemikiran Keislaman, 2023)
Indonesia is a country that has cultural, ethnic and religious diversity. In such a multi-dimensional society, tensions and conflicts often occur between ethnic, religious, racial and cultural groups (SARA) which have an impact on the harmony of life. This research aims to see how the concept and practice of religious moderation from an Islamic perspective can be applied in a pluralistic Indonesian society. This type of research is qualitative research using the literature review method. The conclusion of this study is that an attitude of religious moderation takes the form of recognizing the existence of other parties, having a tolerant attitude, respecting differences of opinion and not imposing personal will. In Islam, the values ​​of religious moderation are known as the concept of tawasuth (moderation), which includes several pillars, namely tasamuh (tolerance), tawazun (balance) and i'tidal (justice and equality). Alquran reminds Muslims not to overdo their religion or be extreme (ghuluw).